Factors Influencing Active Learning in Small Enterprises - Geof Hawke (Adult Education Research Conference, 2000)
Small enterprises are not large users of structured training. However, they are often actively engaged in learning. Is there a framework that identifies the sorts of learning they engage in and can this be useful to guide government support? This paper proposes a possible model.